Outcome After Coracoclavicular Ligament Reconstruction for Acromioclavicular Joint Dislocation - Hemant Kumar Gupta (Journal of College of Medical Sciences-Nepal, 2021)
Background Acromioclavicular injuries are common in athletes and road traffic injuries and there are many surgical and non surgical treatment options for it. In this study displaced acromioclavicular injuries ( Rockwood type 3 and 5) are included in the study and treated with anatomic coracoclavicular reconstruction with semi tendinosis graft and the results were evaluated. Methods A hospital based prospective study including 20 cases of AC joint injuries managed with coraco-clavicular reconstruction using semi tendinosis graft over a period period of March, 2017 to February, 2020 with the mean follow-up duration of 13.5 months was performed. The final outcome was evaluated on the basis of radiological finding and clinically by Constant Murley score and Simple shoulder test. Results At final follow up, radiologically there was average loss of reduction of 3.5 mm ± 0.85mm only as compared to immediate post operative finding. The Clinical outcome measured according to Constant Murley score was 91.2±10.75 (range 86.4-95.5) and according to Simple shoulder test, it was 11.4±3.1 (range 8.5-12.1). overall, the results were satisfactorily with no obvious impairment of shoulder function. Conclusions Coracoclavicular reconstruction using semi Tendinosus from same patient has good outcome both clinically and radiologically in displaced high grade AC joint injuries